2010
DOI: 10.1080/19406940.2010.507209
|View full text |Cite
|
Sign up to set email alerts
|

The effect of management types on the performance of English public sports centres

Abstract: There has been a change in the management of public sports centres in England, with significant numbers being transferred to non in-house operators. This paper analyses the consequences of this change, by evaluating the variation in public sports centre performance by different management types. It uses data on 260 sports centres that undertook the National Benchmarking Service, which has indicators on access to centres by different types of user, finance, utilization, and customer satisfaction. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Liu et al [28] utilized the output-oriented DEA, including operating expenditure, operating hours, and space as three inputs, and revenue and number of participants as two outputs, to assess the operating performances of sport facilities and swimming pools in the UK's National Benchmark Service database. Kung and Taylor [5] also used operational data of sports facilities from the UK's National Benchmarking Service, indicating empirical results in which customer satisfaction is higher for SLCs managed by the government; however, the financial performance of government-owned SLCs is lower compared to SLCs managed by private companies.…”
Section: Performance Assessment For Sport and Leisure Centresmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al [28] utilized the output-oriented DEA, including operating expenditure, operating hours, and space as three inputs, and revenue and number of participants as two outputs, to assess the operating performances of sport facilities and swimming pools in the UK's National Benchmark Service database. Kung and Taylor [5] also used operational data of sports facilities from the UK's National Benchmarking Service, indicating empirical results in which customer satisfaction is higher for SLCs managed by the government; however, the financial performance of government-owned SLCs is lower compared to SLCs managed by private companies.…”
Section: Performance Assessment For Sport and Leisure Centresmentioning
confidence: 99%
“…Hence, how to benchmark success for sports and leisure centers (SLCs) is also one of the most important empirical topics from the commercial enterprise and government perspectives. Kung and Taylor [5] documented that over 60% of local authorities' leisure department net expenditures in the United Kingdom go to indoor sports facilities. They indicated that indoor sports facility investment is mandatory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NBS and CERM-PI) and conducting research based on these has led to an evolution in research on indicators and the technical operations of sports facilities. For example, in the UK, the NBS has been used to examine the operational efficiency of sports facilities (Liu et al 2007), the influence of ownership (Kung and Taylor 2010), the influence of quality awards for sports facility performance (Ramchandani and Taylor 2011) and sports facility performance in times of austerities (Ramchandani et al 2018). In addition, NBS data has been used to investigate customer satisfaction in sports facilities (Liu et al 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The unified concept of the sport movement determined the future direction of facilities development, with a privileged position of organized sport (Sekot, 2010;Špaček, 2011). Thus, while the development of sport facilities in the 1960s and 1970s was associated with decentralization and depoliticization of public administration within Scandinavian countries or the United Kingdom (Rafoss & Troelsen, 2010;Kung & Taylor, 2010), sport facilities in the current territory of the Czech Republic arose from central planning during the same period.…”
Section: Historical Contextmentioning
confidence: 99%